ประสิทธิภาพ ปัญหาอุปสรรค และแนวทางการพัฒนาพื้นที่สีเขียวอย่างยั่งยืนในเขตเทศบาลนครเชียงใหม่ - อุบลรัตน์ หยาใส่ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The 4 objectives of this study were to 1) collect data on policy, work plan and green space development projects in Chiang Mai municipal area; 2) survey the population’s opinions in relation to efficiency evaluation of the green space development projects parks and other types of green space; 3) survey the population’s satisfaction toward the service facilities of the public; and 4) determine problems, difficulties and ways of sustainable development of green spaces. The study was consisted of 504 samples for questionnaires and 20 samples for interview. The research instruments included questionnaire, interview form and field checklist. Then, the qualitative data was analyzed by content analysis and the quantitative data was analyzed by descriptive statistics. The study results were concluded as followed: 1) During the past 10 years there were 3 policies, 2 work plans and 18 projects on green space development which were run by central and local government agencies and private sector. 2) The highest efficient green space development projects was “Na Baan Na Mong activity". Meanwhile, "Tattang Kingmai/Tonmai project" was evaluated as the lowest efficient project. The efficiency average score of all 10 projects was at the fair level. 3) Private sector green space development such as "golf courts", "museums", "hotel gardens" were evaluated as the highest efficient green space. Whereas government's green space development such as "space on the roadsides" or "street isles" were evaluated as lowest efficient ones. 4) The highest satisfaction public parks were "Phra Srinagarindra Boromarajajonani health Park" and "Huay Kaew botanic garden". The lowest satisfaction of public park was "Bridge neck HM The King Honor Celebration Park". 5) problems and difficulties of green space development were public relation shortage, service facilities were not met the standard requirements, lack of maintenance of the equipment and landscape, insufficient personnel and limited budget as well as knowledge technology. 6) The proposed of sustainable development ways were to encourage the participation of the population, community, educational institutes and private sector's roles to moderate the mentioned problems and difficulties to as well as to implicate the research results for further study to gain maximum outcomes.